A biomass-based organic-inorganic composite proton exchange membrane and preparation method thereof

By dispersing the mesoporous zirconia-silica composite in the chitosan matrix, a biomass-based organic-inorganic composite proton exchange membrane was prepared, which solved the problem of poor performance of the existing proton exchange membrane at high temperature and low humidity, and achieved the improvement of high proton conductivity and mechanical properties.

CN115732729BActive Publication Date: 2025-03-21HUBEI ENG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211526855.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-03-21
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

Among the existing proton exchange membrane fuel cells, the commercial Nafion series membranes have problems such as high price, high methanol permeability and poor performance at high temperature and low humidity. At the same time, the untreated chitosan has low proton conductivity and poor mechanical properties and thermal stability.

Method used

A biomass-based organic-inorganic composite proton exchange membrane is used to form a composite membrane by dispersing the mesoporous zirconia-silica composite in the chitosan matrix. The preparation method of the composite membrane includes the steps of forming a template solution, hydrothermal reaction, filtration and drying, cross-linking, etc.

Benefits of technology

The proton conductivity and mechanical properties of the composite membrane were significantly improved, with the proton conductivity increased by 78.6% at 80°C, the mechanical strength increased by 31.3% to 85.71%, and better performance in high temperature and low humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115732729B_ABST
    Figure CN115732729B_ABST
Patent Text Reader

Abstract

The present invention relates to a biomass-based organic-inorganic composite proton exchange membrane and a preparation method thereof, and belongs to the field of proton exchange membrane fuel cells. The preparation method of the present invention comprises the following steps: (1) mesoporous sulfidized zirconium oxide-silicon oxide (SZrSi) is prepared by a two-step method; (2) the prepared mesoporous SZrSi powder is infiltrated and dispersed in a chitosan membrane matrix, and then cast and dried to obtain a dry membrane; (3) the obtained dry membrane is alkali-washed and then washed with water to neutrality, and then placed in a sulfuric acid solution for cross-linking to obtain a composite proton exchange membrane with different inorganic content. The biomass-based organic-inorganic composite proton exchange membrane provided by the present invention has a greatly increased specific surface area of ​​sulfidized zirconium oxide because the sulfided zirconium oxide is supported on mesoporous silica, giving play to its proton conduction advantage, while significantly improving the dispersibility of the inorganic component, enhancing the mechanical properties of the chitosan matrix, and having broad application prospects in polymer-based fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and more specifically to a biomass-based organic-inorganic composite proton exchange membrane and a preparation method thereof. Background Art

[0002] Energy crisis and environmental pollution have become global problems that need to be solved urgently. Fuel cells, as a new type of power generation device, have outstanding features such as high energy conversion efficiency, simple structure, easy operation, zero pollution and zero emission, and play an increasingly important role in the energy field. According to the different types of fuel cell electrolytes, fuel cells can be divided into five categories: proton exchange membrane fuel cells, alkaline fuel cells, solid oxide fuel cells, phosphoric acid fuel cells and molten carbonate fuel cells. Compared with other categories, proton exchange membrane fuel cells have the advantages of low operating temperature, fast start-up speed at room temperature, simple structure, no electrolyte loss, high specific power and specific energy, easy operation, and long service life. It is an ideal power source for decentralized power stations, mobile power supplies, electric vehicles, mobile communications, etc., and is also the best home power source.

[0003] The main components of a proton exchange membrane fuel cell include: proton exchange membrane, catalyst layer, gas diffusion layer and bipolar plate. Among them, the proton exchange membrane is the core component of the proton exchange membrane fuel cell and plays a vital role in the battery performance. At present, the commercialized proton exchange membranes are mainly the Nafion series perfluorosulfonic acid membranes of DuPont in the United States. Although this type of membrane has high proton conductivity, good chemical stability and mechanical properties, it is extremely expensive, has high methanol permeability and poor performance under high temperature and low humidity. Therefore, the preparation of proton exchange membranes with excellent performance and low price has become the focus of fuel cell research.

[0004] As a natural polymer material, chitosan has become a hot topic in recent years due to its stable structure, good film-forming properties, low methanol permeability, excellent compatibility, degradability, and can be used in high temperature and low humidity environments. It is also cheap and easy to be chemically modified. However, untreated chitosan has problems such as low proton conductivity, poor mechanical properties and thermal stability, and often needs to be modified. Zirconia sulfide is a solid superacid catalyst, and its acidity is 10,000 times stronger than concentrated sulfuric acid. Therefore, it is expected to be used as a proton conductor in the field of proton exchange membranes. However, zirconium oxide sulfide powder is very easy to agglomerate and difficult to disperse in the polymer matrix, which limits its acidity. Therefore, how to effectively utilize the acidity and proton conductivity of zirconium oxide sulfide to modify the biomass matrix chitosan and obtain a composite proton exchange membrane with both high proton conductivity and mechanical properties has become the key to the research.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a biomass-based organic-inorganic composite proton exchange membrane and a preparation method thereof.

[0007] In order to achieve the above-mentioned purpose of the invention, the present invention provides a biomass-based organic-inorganic composite proton exchange membrane, wherein the composite proton exchange membrane comprises a biomass matrix chitosan and an inorganic additive mesoporous sulfided zirconium oxide-silicon oxide composite, wherein the mesoporous sulfided zirconium oxide-silicon oxide composite is dispersed in the chitosan matrix, and its addition amount is 0.5wt.%-15wt.% of the chitosan, and preferably, the addition amount is 1wt% to 7wt.% of the chitosan.

[0008] The method for preparing the biomass-based organic-inorganic composite proton exchange membrane provided by the present invention specifically comprises the following steps:

[0009] (1) dissolving the template in a 1-3 mol / L hydrochloric acid aqueous solution to form a solution with a concentration of 1 wt.% to 5 wt.%, and then slowly adding tetraethyl orthosilicate dropwise thereto, controlling the volume ratio of tetraethyl orthosilicate to the hydrochloric acid aqueous solution to be 1:8 to 1:15, stirring at 30° C. to 50° C. for 2 to 5 hours to obtain a turbid mixed solution;

[0010] The template agent is any one of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polyethylene glycol, and dodecylamine; preferably, the template agent is polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer;

[0011] (2) Add a certain amount of zirconium oxychloride (ZrOCl) to the turbid mixed solution obtained in step (1) 2 8H 2 O), wherein the molar ratio of tetraethyl orthosilicate to Si / Zr in zirconium oxychloride is 2-5, and the mixture is stirred at 30-50°C for 15 hours. The mixture is placed in a hydrothermal reactor and reacted at 100-150°C for 24-48 hours. The reactor is taken out and cooled to room temperature, and ammonia (NH 3 ·H 2 O) adjusting the pH to 7-8, placing the reactor back into an oven at 100-150° C., and continuing the reaction for 24-48 hours to obtain a hydrothermal reaction product;

[0012] Preferably, the molar ratio of Si / Zr in tetraethyl orthosilicate and zirconium oxychloride is 4 to 5; more preferably, the molar ratio of Si / Zr is 4;

[0013] (3) filtering the hydrothermal reaction product obtained in step (2), repeatedly washing with a large amount of deionized water, and drying, soaking the obtained powder in a 0.5-2 mol / L sulfuric acid solution at room temperature for 30-60 min, controlling the ratio of the powder sample to the sulfuric acid solution to be 1 g / 10 mL-1 g / 30 mL, filtering, washing, and drying the soaked sample, and finally calcining at 500° C.-650° C. for 2-5 h to obtain a mesoporous sulfidized zirconium oxide-silicon oxide composite (SZrSi);

[0014] (4) dispersing the SZrSi obtained in step (3) in water or ethanol to prepare a SZrSi dispersion having a concentration of 0.5 mg / mL to 10 mg / mL;

[0015] (5) dissolving chitosan in a 1-3 vol.% acetic acid aqueous solution to prepare a chitosan solution with a concentration of 0.5 wt.% to 5 wt.%, adding the SZrSi dispersion prepared in step (4) to the chitosan solution, and mixing thoroughly to obtain a uniform dispersion;

[0016] (6) casting the uniform dispersion obtained in step (5) onto a clean glass plate to form a film, drying it, cooling it to room temperature, and removing the film;

[0017] (7) Soak the dry film obtained in step (7) in a 2-5 mol / L NaOH solution for 2-6 hours to remove residual acetic acid in the film, and then wash it with deionized water. Then transfer the film to a 0.1-4 mol / L sulfuric acid solution and soak it at room temperature for 0.5-5 hours to crosslink the composite membrane. The crosslinked membrane is repeatedly rinsed with deionized water and then dried to obtain a biomass-based organic-inorganic composite membrane.

[0018] Application of the biomass-based organic-inorganic composite proton exchange membrane prepared by the above method in fuel cells.

[0019] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:

[0020] 1. The biomass-based organic-inorganic composite proton exchange membrane provided by the present invention has a greatly increased specific surface area of ​​zirconia sulfide because the zirconia sulfide is supported on mesoporous silica, thereby fully exposing the acid sites of zirconia sulfide and exerting its proton conduction advantage. Therefore, the addition of a very small amount (1%) of mesoporous zirconia sulfide-silicon oxide composite can increase the proton conductivity of the composite membrane at 80°C by 78.6% relative to that of pure chitosan membrane; under the condition of the same addition amount, the proton conductivity of the composite membrane at 80°C is increased by 85.4% and 47.6% compared with chitosan / mesoporous silica and chitosan / zirconia sulfide composite membranes, respectively;

[0021] 2. The biomass-based organic-inorganic composite proton exchange membrane provided by the present invention has significantly improved the dispersibility of the inorganic component and enhanced the mechanical properties of the chitosan matrix because the sulfide zirconium oxide is supported on the mesoporous silica. When the inorganic component is added in an amount of 1%, its mechanical strength can be as high as 34.17MPa, which is 31.3% higher than the 26.03MPa of the pure chitosan membrane; when the addition amount is 5%, its mechanical strength can be as high as 48.34MPa, which is 85.71% higher than the pure chitosan membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the small-angle X-ray diffraction pattern of the mesoporous SZrSi prepared in Example 3.

[0023] Figure 2 This is the TEM photo of the mesoporous SZrSi prepared in Example 3. DETAILED DESCRIPTION

[0024] The applicant further describes the technical solution of the present invention in combination with specific embodiments and drawings below, but the present invention is not limited to these embodiments.

[0025] Drug description: Polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was purchased from McLean Co., Ltd.; tetraethyl orthosilicate was purchased from Anage Chemical Reagent Co., Ltd.; zirconium oxychloride, ammonia water, hydrochloric acid, sodium hydroxide, acetic acid, and ethanol were purchased from Sinopharm Chemical Reagent Co., Ltd.; chitosan with a molecular weight of 1 million and a deacetylation degree of 90% was purchased from Zhejiang Aoxing Biological Co., Ltd.

[0026] Example 1

[0027] The composite proton exchange membrane was prepared according to the mass ratio of mesoporous sulfidized zirconium oxide-silicon oxide to chitosan being 1:100. The specific operation process is as follows:

[0028] 0.8 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 25 ml of 2 mol / L hydrochloric acid solution, and 2 ml of tetraethyl orthosilicate (Si(OCH 2 CH 3 ) 4 , 9 mmol), stirred at 40 ° C for 3 to 4 h, and when the solution became turbid, 1.450 g zirconium oxychloride (ZrOCl 2 8H 2 O, 4.5 mmol), wherein Si / Zr=2 (molar ratio), and continued stirring at 40°C for 15 h. The above reaction mixture was placed in a reactor and reacted at 100°C for 48 h. The reactor was taken out and cooled to room temperature, and the reactor was opened and ammonia (NH 3 ·H 2O) adjust pH = 7-8, put the reactor back into the 100 ° C oven, take out the reactor after 48 hours, filter the product, repeatedly wash and dry it with a large amount of deionized water to obtain a powder; the powder is then immersed in 0.5 mol / L sulfuric acid solution for 60 minutes (about 15 ml of sulfuric acid solution per gram of sample), the obtained product is filtered and dried, and then calcined at 650 ° C for 3 hours to obtain a mesoporous sulfide zirconium oxide-silicon oxide composite (SZrSi) material.

[0029] Weigh 0.7g chitosan into a beaker, add 20mL of 2vt% acetic acid solution, ultrasonically and stir for 10h to completely dissolve. Weigh 7mg of the mesoporous SZrSi powder prepared above into another beaker, add 10ml of anhydrous ethanol, and ultrasonically disperse. Mix, ultrasonicate and stir the two solutions to form a uniform solution, ultrasonicate for 30min, and let stand to degas. Cast the obtained uniform dispersion onto a clean glass plate and dry at 40°C to obtain a dry film. Subsequently, soak the obtained dry film in 5mol / L NaOH solution for 3h to remove residual acetic acid in the film, and then wash with deionized water. Then put the membrane into 2mol / L H 2 SO 4 The CS / SZrSi-1% composite proton exchange membrane was obtained by drying at 40°C for 48 hours.

[0030] Example 2

[0031] According to the mass ratio of SZrSi to chitosan being 3:100, a composite proton exchange membrane CS / SZrSi-3% was prepared. The specific operation process is as follows:

[0032] 0.8 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 25 ml of 1 mol / L hydrochloric acid solution, and 3 ml of tetraethyl orthosilicate (Si(OCH 2 CH 3 ) 4 , 13.5mmol), stirred at 30℃ for 4-5h, when the solution became turbid, 1.450g zirconium oxychloride (ZrOCl 2 8H 2 O, 4.5 mmol), wherein Si / Zr=3 (molar ratio), and continued stirring at 30°C for 15 h. The above reaction mixture was placed in a reactor and reacted at 120°C for 36 h. The reactor was taken out and cooled to room temperature, and the reactor was opened and ammonia (NH 3 ·H 2O) adjust pH = 7-8, put the reactor back into the 120 ° C oven, take out the reactor after 36 hours, filter the product, repeatedly wash and dry it with a large amount of deionized water to obtain a powder; the powder is then immersed in 1 mol / L sulfuric acid solution for 30 minutes (about 15 ml of sulfuric acid solution per gram of sample), the obtained product is filtered and dried, and then calcined at 600 ° C for 4 hours to obtain the mesoporous SZrSi material.

[0033] Weigh 0.7g chitosan into a beaker, add 25mL of 1vt% acetic acid solution, and stir and sonicate until completely dissolved. Weigh 21mg of the SZrSi powder prepared above into another beaker, add 10ml of ethanol, and disperse by sonication. Mix, sonicate, and stir the two solutions until a uniform solution is formed, sonicate for 20min, and let stand to degas. Cast the resulting uniform dispersion onto a clean glass plate and dry at 40°C to obtain a dry film. Subsequently, soak the resulting dry film in a 2mol / L NaOH solution for 6h to remove residual acetic acid in the film, and then wash with deionized water. Then place the film in a 2mol / L H 2 SO 4 The CS / SZrSi-3% composite proton exchange membrane was obtained by drying at 40°C for 48 hours.

[0034] Example 3

[0035] The composite proton exchange membrane was prepared according to the mass ratio of SZrSi to chitosan being 5:100. The specific operation process is as follows:

[0036] 0.8 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 25 ml of 2 mol / L hydrochloric acid solution, and 3 ml of tetraethyl orthosilicate (Si(OCH 2 CH 3 ) 4 , 13.5mmol), stirred at 50℃ for 3-4h, when the solution became turbid, 1.088g zirconium oxychloride (ZrOCl 2 8H 2 O, 3.4 mmol), wherein Si / Zr=4 (molar ratio), and continued stirring at 50°C for 15 h. The above reaction mixture was placed in a reactor and reacted at 140°C for 24 h. The reactor was taken out and cooled to room temperature, and the reactor was opened and ammonia (NH 3 ·H 2O) adjust pH = 7-8, put the reactor back into the 140 ° C oven, take out the reactor after 24 hours, filter the product, repeatedly wash and dry it with a large amount of deionized water to obtain a powder; the powder is then immersed in 1.5 mol / L sulfuric acid solution for 30 minutes (about 15 ml of sulfuric acid solution per gram of sample), the obtained product is filtered and dried, and then calcined at 600 ° C for 4 hours to obtain the mesoporous SZrSi material.

[0037] Weigh 0.7g chitosan into a beaker, add 25mL of 2vt% acetic acid solution, and stir and sonicate until completely dissolved. Weigh 35mg of the SZrSi powder prepared above into another beaker, add 10ml of ethanol, and disperse by sonication. Mix, sonicate, and stir the two solutions until a uniform solution is formed, sonicate for 30min, and let stand to degas. Cast the resulting uniform dispersion onto a clean glass plate and dry at 40°C to obtain a dry film. Subsequently, soak the resulting dry film in a 5mol / L NaOH solution for 3h to remove residual acetic acid in the film, and then wash with deionized water. Then place the film in a 2mol / L H 2 SO 4 The CS / SZrSi-5% composite proton exchange membrane was obtained by drying at 40°C for 48 hours.

[0038] Figure 1 This is the small angle X-ray diffraction pattern of the mesoporous SZrSi prepared in Example 3. Figure 1 It can be seen that the mesoporous sulfided zirconium oxide-silicon oxide composite prepared in Example 3 has an obvious diffraction peak at 2θ=1.28°, which is a diffraction peak of ordered mesopores peculiar to mesoporous materials.

[0039] Figure 2 This is a TEM image of the mesoporous SZrSi prepared in Example 3. From the results, it can be seen that there are a large number of pores with a size of ~5 nm on the surface of the composite.

[0040] Example 4

[0041] The composite proton exchange membrane was prepared according to the mass ratio of SZrSi to chitosan being 7:100. The specific operation process is as follows:

[0042] 0.8 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 25 ml of 2 mol / L hydrochloric acid solution, and 2 ml of tetraethyl orthosilicate (Si(OCH 2 CH 3 ) 4 , 9 mmol), stirred at 40 ° C for 3 to 4 h, and when the solution became turbid, 0.580 g zirconium oxychloride (ZrOCl 2 8H2 O, 1.8 mmol), wherein Si / Zr=5 (molar ratio), and continued stirring at 40°C for 15 h. The above reaction mixture was placed in a reactor and reacted at 150°C for 24 h. The reactor was taken out and cooled to room temperature, and the reactor was opened and ammonia (NH 3 ·H 2 O) adjust pH = 7-8, put the reactor back into the 150 ° C oven, take out the reactor after 24 hours, filter the product, repeatedly wash and dry it with a large amount of deionized water to obtain a powder; the powder is then immersed in 2 mol / L sulfuric acid solution for 30 minutes (about 15 ml of sulfuric acid solution per gram of sample), the obtained product is filtered and dried, and then calcined at 600 ° C for 4 hours to obtain the mesoporous SZrSi material.

[0043] Weigh 0.7g chitosan into a beaker, add 30mL of 2vt% acetic acid solution, and ultrasonically stir until completely dissolved. Weigh 49mg of the SZrSi powder prepared above into another beaker, add 10ml of ethanol, and ultrasonically disperse. Mix, ultrasonically and stir the two solutions to form a uniform solution, ultrasonicate for 30min, and let stand to degas. Cast the obtained uniform dispersion onto a clean glass plate and dry at 40°C to obtain a dry film. Subsequently, soak the obtained dry film in a 2mol / L NaOH solution for 6h to remove residual acetic acid in the film, and then wash with deionized water. Then put the film into a 2mol / L H 2 SO 4 The CS / SZrSi-7% composite proton exchange membrane was obtained by drying at 40°C for 48 hours.

[0044] Comparative Example 1

[0045] The preparation of pure chitosan film, the specific operation process is as follows:

[0046] Weigh 0.7g chitosan into a beaker, add 25mL of 1vt% acetic acid solution, and stir for 12h to completely dissolve. Ultrasonicate and let stand to degas. Cast the obtained uniform dispersion onto a clean glass plate and dry at 40°C to obtain a dry film. Then, soak the obtained dry film in 5mol / L NaOH solution for 3h to remove the residual acetic acid in the film, and then wash it with deionized water. Then put the obtained film into 2mol / L H 2 SO 4 The CS membrane was cross-linked in the solution for 3 h and washed with deionized water until neutral. Finally, it was dried at 40 °C for 48 h to obtain a pure CS membrane.

[0047] Comparative Example 2

[0048] Add mesoporous silica to prepare a composite proton exchange membrane. The specific operation process is as follows:

[0049] 0.8 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 25 ml of 2 mol / L hydrochloric acid solution, and 2 ml of tetraethyl orthosilicate (Si(OCH 2 CH 3 ) 4 ), stirred at 40℃ for 24h. The above reaction mixture was placed in a reactor and reacted at 100℃ for 48h. The reactor was taken out and cooled to room temperature. The product was filtered, repeatedly washed with a large amount of deionized water and dried to obtain a powder; and then calcined at 500℃ for 5h to obtain a mesoporous silica material.

[0050] Weigh 0.7g chitosan into a beaker, add 20mL of 2vt% acetic acid solution, ultrasonically and stir for 10h to completely dissolve. Weigh 7mg of the mesoporous silica powder prepared above into another beaker, add 10ml of ethanol, and ultrasonically disperse. Mix, ultrasonically and stir the two solutions to form a uniform solution, ultrasonicate for 30min, and let stand to degas. Cast the obtained uniform dispersion onto a clean glass plate and dry at 40°C to obtain a dry film. Subsequently, soak the obtained dry film in 5mol / L NaOH solution for 3h to remove residual acetic acid in the film, and then wash with deionized water. Then put the membrane into 2mol / L H 2 SO 4 The CS / SiO2 solution was cross-linked for 3 h and then washed with deionized water until neutral. Finally, it was dried at 40 °C for 48 h to obtain CS / SiO2. 2 -1% composite proton exchange membrane.

[0051] Comparative Example 3

[0052] Add sulfide zirconium oxide to prepare a composite proton exchange membrane. The specific operation process is as follows:

[0053] 2.5 g zirconium oxychloride (ZrOCl 2 8H 2 O) was dissolved in 25 ml of deionized water and stirred at 40 ° C for 6 hours. Then, an appropriate amount of ammonia water was added dropwise to the solution until the pH of the solution was 7-8, and a precipitate was produced. After stirring for 4 hours, the product was filtered and repeatedly washed with a large amount of deionized water. After the obtained powder was dried, it was immersed in 0.5 mol / L sulfuric acid solution for 30 minutes (about 15 ml of sulfuric acid solution per gram of sample). The obtained powder was filtered and dried, and calcined at 650 ° C for 3 hours to obtain sulfide zirconium oxide material.

[0054] Weigh 0.7g of chitosan into a beaker, add 20mL of 2vt% acetic acid solution, and ultrasonically stir for 10h to completely dissolve. Weigh 7mg of the above-prepared zirconium oxide sulfide powder into another beaker, add 10ml of ethanol, and ultrasonically disperse. Mix, ultrasonicate and stir the two solutions to form a uniform solution, ultrasonicate for 30min, and let stand to degas. Cast the obtained uniform dispersion onto a clean glass plate and dry at 40°C to obtain a dry film. Subsequently, soak the obtained dry film in 5mol / L NaOH solution for 3h to remove residual acetic acid in the film, and then wash with deionized water. Then put the membrane into 2mol / L H 2 SO 4 The CS / SZr-1% composite proton exchange membrane was obtained by drying at 40°C for 48 hours.

[0055] The mechanical properties and proton conductivity of the composite proton exchange membranes provided in Examples 1 to 4 of the present invention and Comparative Examples 1 to 3 were tested in the same temperature and humidity environment. The results are shown in Tables 1 and 2.

[0056] The specific test parameters are as follows:

[0057] 1. Mechanical properties test:

[0058] The room temperature mechanical strength of the dry film (width × length = 1 × 4 cm) was measured on a mechanical tester (XLW(EC)-A, Jinan Blue Light Electromechanical Technology Co., Ltd.) at a tensile speed of 10 mm min -1 , temperature 25℃, relative humidity 63%. Each film sample was measured 3 times and the average value was taken.

[0059] 2. Proton conductivity test:

[0060] The electrochemical impedance spectroscopy was used to measure the concentration of the samples at 5 mV and 1-10 Hz. 6 Hz frequency range, the ionic conductivity of the membrane in the fully hydrated state was tested. By controlling the temperature, the electrochemical impedance spectroscopy (EIS) under different conditions can be obtained, and the ionic conductivity of the membrane σ (S·cm -1 ), which can be calculated by the following formula:

[0061]

[0062] Where L (cm) is the distance between the two electrodes, A (cm 2 ) is the effective cross-sectional area of ​​the film to be tested, and R (Ω) is the film resistance obtained by the intersection of the curve in the obtained Nyquist plot with the real axis in the high frequency region.

[0063] Table 1 Mechanical properties test results of composite proton exchange membrane

[0064]

[0065] Table 2 Proton conductivity of composite membranes at different temperatures

[0066]

[0067]

Claims

1. A method for preparing a biomass-based organic-inorganic composite proton exchange membrane, characterized in that: The preparation method of the composite proton exchange membrane comprises the following steps: uniformly dispersing a mesoporous sulfide zirconium oxide-silicon oxide composite in an acetic acid aqueous solution of chitosan, casting the obtained dispersion into a membrane, alkali washing, washing with water to neutrality, and then immersing in a sulfuric acid solution for cross-linking, washing with water and drying to obtain the composite proton exchange membrane; the composite proton exchange membrane comprises a biomass matrix chitosan and an inorganic additive mesoporous sulfide zirconium oxide-silicon oxide composite dispersed in the chitosan matrix; the addition amount of the mesoporous sulfide zirconium oxide-silicon oxide composite is 0.5wt.%-15wt.% of the chitosan; The method for preparing the mesoporous sulfided zirconium oxide-silicon oxide composite comprises the following steps: (1) Dissolve the template in a 1-3 mol / L hydrochloric acid aqueous solution to form a solution with a concentration of 1 wt.%-5 wt.%, then slowly add tetraethyl orthosilicate dropwise thereto, control the volume ratio of tetraethyl orthosilicate to the hydrochloric acid aqueous solution to be 1:8-1:15, and stir at 30°C-50°C for 2-5 h to obtain a turbid mixed solution; The template agent is any one of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polyethylene glycol, and dodecylamine; (2) adding a certain amount of zirconium oxychloride to the turbid mixed solution obtained in step (1), wherein the molar ratio of tetraethyl orthosilicate to Si / Zr in zirconium oxychloride is 2-5, and continuing to stir at 30°C-50°C for 15 h. The obtained mixed solution is charged into a hydrothermal reaction kettle and reacted at 100°C-150°C for 24-48 h. The reaction kettle is taken out and cooled to room temperature. The reaction kettle is opened and the pH is adjusted to 7-8 with aqueous ammonia. The reaction kettle is put back into an oven at 100°C-150°C and the reaction is continued for 24-48 h to obtain a hydrothermal reaction product. (3) The hydrothermal reaction product obtained in step (2) is filtered, repeatedly washed with a large amount of deionized water, and dried. The resulting powder is then soaked in a 0.5-2 mol / L sulfuric acid solution at room temperature for 30-60 min, and the ratio of the powder sample to the sulfuric acid solution is controlled to be 1 g / 10 mL to 1 g / 30 mL. The soaked sample is filtered, washed, and dried, and finally calcined at 500-650° C. for 2-5 h to obtain a mesoporous sulfide zirconium oxide-silicon oxide composite.

2. The preparation method according to claim 1, characterized in that: The preparation method of the mesoporous sulfided zirconia-silicon oxide composite is characterized in that the addition amount of the mesoporous sulfided zirconia-silicon oxide composite is 1wt.%~7wt.% of chitosan.

3. The preparation method according to claim 1 or 2, characterized in that: In the method for preparing the mesoporous sulfided zirconium oxide-silicon oxide composite, in step (2), the molar ratio of Si / Zr is 4-5.

4. The preparation method according to claim 3, characterized in that: The method for preparing the composite proton exchange membrane comprises the following steps: (1) dispersing the mesoporous sulfide zirconium oxide-silicon oxide composite in water or ethanol to prepare a dispersion with a concentration of 0.5 mg / mL to 10 mg / mL; (2) dissolving chitosan in a 1-3 vol.% acetic acid aqueous solution to prepare a chitosan solution with a concentration of 0.5 wt.% to 5 wt.%, adding the mesoporous sulfide zirconium oxide-silicon oxide composite dispersion prepared in step (1) to the chitosan solution, and mixing thoroughly to obtain a uniform dispersion; (3) casting the uniform dispersion obtained in step (2) onto a clean glass plate to form a film, drying it, cooling it to room temperature and then removing the film; (4) Soaking the dry membrane obtained in step (3) in a 2-5 mol / L NaOH solution for 2-6 h to remove residual acetic acid in the membrane, then washing it with deionized water, and then transferring the membrane to a 0.1-4 mol / L sulfuric acid solution and soaking it at room temperature for 0.5-5 h to cross-link the composite membrane. The cross-linked membrane is repeatedly rinsed with deionized water and then dried to obtain a biomass-based organic-inorganic composite membrane.

5. Use of the biomass-based organic-inorganic composite proton exchange membrane prepared by the method according to any one of claims 1 to 4 in a fuel cell.

Citation Information

Patent Citations

  • Composite alkaline polyelectrolyte membrane, preparation method thereof and alkaline polyelectrolyte fuel cell

    CN107195937A

  • Preparation method of proton exchange membrane and fuel cell

    CN113178604A